Biochemical studies on the activity of delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine synthetase from Streptomyces clavuligerus. - Zhang, J (1992)
The enzyme activity of purified delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine (ACV) synthetase from Streptomyces clavuligerus was studied biochemically. The dependence of ACV synthetase activity on reaction parameters, including substrates, cofactors, temperature and pH, were determined, resulting in a substantially increased enzyme activity. The activity is very labile to high temperature and is also unstable at acidic pH. The enzyme specificity is strict towards L-alpha-aminoadipate, but rather loose with respect to L-valine; certain modifications of L-cysteine can also be tolerated. Some unnatural tripeptides synthesized by ACV synthetase can be converted into bioactive compounds by isopenicillin N synthase. The only nutrient found to negatively affect ACV synthetase activity is phosphate, but various compounds such as thiol-blocking reagents and ATP-utilization products (AMP and pyrophosphate) are inhibitory to the enzyme.